EXPLORING LEADERSHIP BEHAVIOURS THAT SHAPE SAFETY PERFORMANCE: A TRANSFORMATIONAL LENS - Mustapha, Nadwatul Husna; Che Malek, Mazlina (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study examines the role of transformational leadership in improving employee safety through elements of motivation, guidance, enforcement, support for employees, and monitoring. Transformational leadership plays a key role in influencing employee safety behaviour and performance. By providing inspiration, guidance, and positive role models, transformational leaders can strengthen safety practices in the workplace, as well as ensure employees consistently adhere to established safety procedures. Furthermore, the study also emphasizes the importance of support to workers in the form of ongoing training, adequate rest, and recognition of their efforts, all of which contribute to improved workplace safety. Additionally, effective safety policy enforcement and monitoring, achieved through awareness campaigns, play a crucial role in ensuring employee compliance. The results of this study demonstrate that transformational leadership enhances employee motivation and strengthens the enforcement of safety policies, ultimately leading to an overall increase in employee safety.